Before Harlem : The Black Experience in New York City Before World War I - Sacks, Marcy S. (Book collections on Project MUSE., 2006)
"In the years between 1880 and 1915, New York City and its environs underwent a tremendous demographic transformation with the arrival of millions of European immigrants, native whites from the rural countryside, and people of African descent from both the American South and the Caribbean. While all groups faced challenges in their adjustment to the city, hardening racial prejudices set the black experience apart from that of other newcomers. Through encounters with each other, blacks and whites, both together and in opposition, forged the contours of race relations that would affect the city for decades to come." "Before Harlem reveals how black migrants and immigrants to New York entered a world far less welcoming than the one they had expected to find. White police officers, urban reformers, and neighbors faced off in a hostile environment that threatened black families in multiple ways. Unlike European immigrants, who typically struggled with low-paying jobs but who often saw their children move up the economic ladder, black people had limited employment opportunities that left them with almost no prospects of upward mobility. Their poverty and the vagaries of a restrictive job market forced unprecedented numbers of black women into the labor force, fundamentally affecting child-rearing practices and marital relationships."--Jacket.